SWK-09. Baseline Survey of Hematology/Oncology/Cellular Therapy Staff/Faculty Perceptions of Palliative Care. (3rd June 2022) - Hemenway, Molly; Raybin, Jennifer; Waters, Melissa
Abstract: Recent literature has shown that pediatric oncology patients and families prefer early integration of palliative care, yet the perception persists by staff and providers that palliative care has a negative connotation. We examined the baseline views of staff at our tertiary care center, prior to expansion of a formal palliative care service. We will describe baseline survey results in a diverse group of hematology/oncology/cellular therapy staff/faculty. This quality improvement project was conceived by the unit-based palliative care committee to compare baseline and follow-up survey results. We report the baseline results of a convenience sample of providers with varied roles. A validated survey for staff perception of palliative care found in the literature was utilized. After institutional qualitative review board approval, the survey was emailed to members of the inpatient and outpatient units. Demographic data collected included gender, level of education, role, patient population, length of career globally and locally. Perception of palliative care was evaluated by asking questions regarding 1) overlap with disease focused care, 2) risks/benefits of palliative care, and 3) timing of palliative care consults. Results were tabulated and graphed for dissemination to the unit-based palliative care committee. A follow-up survey is planned after integration of the developing formal palliative care service. Longitudinal comparison with statistical analysis will be completed at that time. Although most participants disagreed that palliative care is not consistent with curative care and that early palliative care does not induce parental anxiety, yet is perceived by the lay public as end-of-life care. Strong agreement was demonstrated with items regarding integration of palliative care early in the disease trajectory to decrease suffering. Participants also predominantly agreed that education for patients/families and staff/faculty would ameliorate misconceptions about palliative care. Future evaluation after increased palliative care penetration will provide comparison data.